Sleep quality and functional gastrointestinal disorders. A psychological issue. Issue 2 (15th March 2018) - Bouchoucha, Michel; Mary, Florence; Bon, Cyriaque; Bejou, Bakhtiar; Airinei, Gheorghe; Benamouzig, Robert
Abstract : OBJECTIVE: Sleep disorders are often associated with functional gastrointestinal disorders (FGIDs). This study aims to evaluate the association of sleep disorders with specific FGIDs and to assess the related importance of psychological disorders. METHODS: We included 1009 consecutive patients with FGIDs (70.9% females). The patients completed a Rome III questionnaire and after a psychological evaluation on anxiety and depression they were classified according to their sleep disorders using a 7‐point grading scale: Groups 1–3, drowsiness (severe, moderate, mild); Group 4, no change; Groups 5–7, insomnia (mild, moderate, severe). Multinomial logistic regression using sleep group as a dependent variable with no sleep change as reference and body mass index, FGIDs, anxiety and depression as independent variables were used for statistical analysis. RESULTS: Altogether 667 (66.1%) patients reported changes in sleep disorders, of whom 487 (48.3%) had decreased sleep and 180 (17.8%) had increased sleep while 342 (33.9%) reported no change. Depression was lower in patients with no change in sleep pattern and increased with the severity of their sleep disorder ( P < 0.001). State‐anxiety is associated with moderate drowsiness ( P = 0.024), while trait anxiety is associated with mild insomnia ( P = 0.048). FGIDs associated with sleep disorders included chest pain, epigastric pain syndrome, irritable bowel syndrome with constipation, diarrhea, bloating, fecal incontinence and proctalgia fugax. CONCLUSION: Sleep disorders are associated with FGIDs, especially in the presence of depressive symptoms.